Investigating the effects of realistic noise on a chaotic semi-express bus system - Ngiam, Li Ting (Nanyang Technological University, 2021)
Efforts to alleviate the repercussions of bus bunching from typical bus loop services motivated the study of bus loops with different degrees of realistic noise. Simple models of normal and semi-express bus loops with 2 buses and 3 bus stops were studied in this project through time-step based simulations. As there is not enough existing evidence to understand the such bus services under the influence of noise, although it exists in reality. Research is necessary for this to bring more attention to such phenomenon and understand the effects of noise on bus bunching. This was done through the implementation of stochastic perturbations of the speed of the moving buses on every discrete timestep in both bus loop types. Through simulations, it was found that noise decreases the overall efficiency of a bus system although the buses in both bus services researched on remain un-bunched for a longer period of time. Average waiting times of passengers do not seem to relate with bunch bunching.